The Right to Be Forgotten versus the Right to Disclosure of Gamete Donors’ ID: Ethical and Legal Considerations - Correia, Mónica; Rego, Guilhermina; Nunes, Rui (Acta Bioethica, 2021)
The anonymity of gamete donors in the context of medically-assisted reproduction techniques (ART) and the right of the offspring to know their genetic or biological parents’ identity is a controversial and widely debated topic in the scientific literature. The positions on the issue in each country are different. Sometimes they are in opposition to each other even in countries with strong similarities, such as those in the European Union (EU), in the framework of shared ethical values. Although some countries still enshrine the rule of anonymity, there is an undeniable tendency to guarantee the right to know one’s origins by creating relevant exceptions or abolishing donor anonymity status altogether. This article offers ethical and legal considerations of whether the so-called ‘right to be forgotten’ (RTBF) could be extended to include gamete donors’ right to remain anonymous. This perspective goes against the general trend, certainly in Europe, of recognizing that offspring born from donor gametes have a right to access information relating to their genetic progenitors. The novel addition is to question whether the General Data Protection Regulation (GDPR) might provide fertile ground for questioning this approach, and effectively support those jurisdictions where anonymity is still possible.